Hyperhomocysteinemia in hypofertile male patients can be alleviated by supplementation with 5MTHF associated with one carbon cycle support - Clement, Arthur; Amar, Edouard; Clement, Patrice; Sedbon, Éric; Brami, Charles; Alvarez, Silvia; Menezo, Yves (Frontiers in Reproductive Health, 2023)
Introduction: Homocysteine (Hcy) is a cellular poison, side product of the hydrolysis of S-Adenosyl Homocysteine, produced after the universal methylation effector S -Adenosylmethionine liberates a methyl group to recipient targets. It inhibits the methylation processes and its rising is associated with multiple disease states and ultimately is both a cause and a consequence of oxidative stress, affecting male gametogenesis. We have determined hyper homocysteinhemia (HHcy) levels can be reliably reduced in hypofertile patients in order to decrease/avoid associated epigenetic problems and protect the health of future children, in consideration of the fact that treatment with high doses of folic acid is inappropriate. Methods: Homocysteine levels were screened in male patients consulting for long-standing infertility associated with at least three failed Assisted Reproductive Technology (ART) attempts and/or repeat miscarriages. Seventy-seven patients with Hcy levels>15µM were treated for three months with a combination of micronutrients including 5- MethylTetraHydroFolate (5-MTHF), the compound downstream to the MTHFR enzyme, to support the one carbon cycle; re-testing was performed at the end of a 3 months treatment period. Genetic status for Methylenetetrahydrofolate Reductase (MTHFR) Single nucleotide polymorphisms (SNPs) 677CT (c.6777C>T) and 1298AC (c.1298A>C) was determined. Results: Micronutrients/5-MTHF were highly efficient in decreasing circulating Hcy, from averages 27.4 to 10.7 µM, with a mean observed decrease of 16.7 µM. The MTHFR SNP 677TT (homozygous form) and combined heterozygous 677CT/1298AC status represent 77.9% of the patients with elevated Hcy. Discussion: Estimation HHcy should not be overlooked in men suffering infertility of long duration. MTHFR SNPs, especially 677TT, are a major cause of high homocysteinhemia (HHcy). In these hypofertile patients, treatment with micronutrients including 5-MTHF reduces Hcy and even allows spontaneous pregnancies post treatment. This type of therapy should be considered in order to ensure these patients’ quality of life and avoid future epigenetic problems in their descendants.